EFFECT OF PROBLEM-BASED LEARNING AND INITIAL ABILITY ON AUTOMOTIVE ENGINEERING LEARNING OUTCOMES - Rufii, Rufii (EDUTECH, 2020)
The purpose of this study was to examine the differences in the effect of Problem Based Learning) and initial abilities on learning achievement on Light Vehicle Engine Maintenance subjects. This study was a quasi-experimental study with 2 x 2 or 22 factorial designs. A total of 127 eleventh-grade vocational high school students of Light Vehicle Engine Maintenance participated in the study. The data were collected by tests and non-tests. They were then analyzed by 2-way ANOVA. The results showed that the studentsâ€™ learning achievement was improved when the teacher applied thd Problem Based Learning model without having to look the at students' initial abilities. This is due to the fact that the learning model and the initial abilities did not have a significant interactional effect on the learning achievement.Â Tujuan penelitian ini adalah untuk menguji perbedaan pengaruh Problem Based Learning) dan kemampuan awal terhadap prestasi belajar pada mata pelajaran Perawatan Mesin Kendaraan Ringan. Penelitian ini merupakan penelitian eksperimen semu dengan desain faktorial 2 x 2 atau 22. Sebanyak 127 siswa SMK Pemeliharaan Mesin Kendaraan Ringan kelas XI ikut serta dalam penelitian tersebut. Pengumpulan data dilakukan dengan tes dan non tes. Mereka kemudian dianalisis dengan 2-way ANOVA. Hasil penelitian menunjukkan bahwa prestasi belajar siswa meningkat ketika guru menerapkan model Problem Based Learning tanpa harus melihat kemampuan awal siswa. Hal ini disebabkan karena model pembelajaran dan kemampuan awal tidak memberikan pengaruh interaksional yang signifikan terhadap prestasi belajar.